New insight into the thermal stability of the amorphous tetraphenyl-diamine (TPD) - A combined calorimetry/in-situ Raman microscopy study - Svoboda, Roman; Krbal, Miloš (Elsevier Science SA, 2024)
Non-isothermal differential scanning calorimetry (DSC) was used to study the influences of particle size d(aver) and heating rate q(+) on the crystal growth and decomposition kinetics of amorphous N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-benzidine (TPD). The macroscopic crystallization kinetics was found to be strongly dependent on q(+). At high q(+), the crystal growth proceeded dominantly from the mechanical defects acting as primary growth centers, with the corresponding activation energy being similar to 70-80 kJ mol(-1). At low q(+), the crystalline phase was primarily formed from heterogeneous nuclei, with the activation energy for the growth process being similar to 980 kJ mol(-1). The prolonged nucleation led to extensive passivation of the surface mechanical defects with respect to their function as direct crystal-growth-accelerating centers. Temperature-resolved in-situ Raman microscopy has confirmed the conclusions derived from the DSC data and helped to identify the residual low-q(+) defects-originating crystal growth as proceeding from volume-located micro-cracks. The X-ray diffraction analysis confirmed that TPD crystallizes into an identical phase under all circumstances. The thermal decomposition of TPD was found to proceed in a single step, by simple nth-order reaction kinetics with the activation energy of similar to 120 kJ mol(-1).
Nový pohled na tepelnou stabilitu amorfního tetrafenyl-diaminu (TPD) - studie pomocí kombinované kalorimetrie/in-situ Ramanova mikroskopie
Keywords: Amorphous TPD; DSC; Crystal growth kinetics; Thermal decomposition; tepelná stabilita; amorfní; tetrafenyl-diamin; DSC; Ramanova mikroskopie